2017
DOI: 10.1186/s12889-017-4649-1
|View full text |Cite
|
Sign up to set email alerts
|

The protective effect of helmet use in motorcycle and bicycle accidents: a propensity score–matched study based on a trauma registry system

Abstract: BackgroundTransportation by motorcycle and bicycle has become popular in Taiwan, this study was designed to investigate the protective effect of helmet use during motorcycle and bicycle accidents by using a propensity score–matched study based on trauma registry system data.MethodsData of adult patients hospitalized for motorcycle or bicycle accidents between January 1, 2009 and December 31, 2015 were retrieved from the Trauma Registry System. These included 7735 motorcyclists with helmet use, 863 motorcyclist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 31 publications
4
23
0
7
Order By: Relevance
“…Furthermore, Chen and Pai [11] indicated that helmet use was beneficial in reducing head or neck injuries among motorcyclists involved in approach-turn crashes. The beneficial effects of helmet use on reducing head or neck injuries have also been well documented in other international studies [6,7,[12][13][14]. Nonetheless, several studies have argued that helmet use was associated with an increased risk of neck injuries.…”
Section: Introductionmentioning
confidence: 68%
See 1 more Smart Citation
“…Furthermore, Chen and Pai [11] indicated that helmet use was beneficial in reducing head or neck injuries among motorcyclists involved in approach-turn crashes. The beneficial effects of helmet use on reducing head or neck injuries have also been well documented in other international studies [6,7,[12][13][14]. Nonetheless, several studies have argued that helmet use was associated with an increased risk of neck injuries.…”
Section: Introductionmentioning
confidence: 68%
“…Studies [1,[5][6][7][8][9] have consistently concluded that helmet use is beneficial in preventing head injuries and subsequently reducing injury severity among motorcyclists. By using police-reported crash data in Taiwan, Keng [10] found that helmet use was associated with a decreased odds of deaths among motorcyclists.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing victims of motorcycle accidents who wore a helmet or not, for example, there were more serious injuries to the head / neck, face, chest and extremities and the occurrence of deaths was significantly higher among motorcycle riders who did not wear a helmet. Regarding the cases of cervical vertebra fractures, this number was also significantly higher concerning those who did not wear a helmet [55].…”
Section: Discussionmentioning
confidence: 87%
“…In Taiwan, nearly 60% of all trauma injuries and driving fatalities involving motorcycle accidents [ 32 ]. It had been reported that, in Taiwan, the mortality rate of motorcyclists using helmets was significantly lower than those not using helmets (1.1% vs. 4.2%, respectively; OR, 0.2; 95% CI, 0.17–0.37; p < 0.001) [ 33 ]. However, in this study, the rates of injuries as a motorcycle pillion in both preschool-aged and school-aged children were higher than that in adult patients.…”
Section: Discussionmentioning
confidence: 99%